Clinical analysis of 125I seed implantation combined with Apatinib in the treatment of locally advanced lung cancer: a case series - Yiling Feng; Bo Yang; Li, Xiaoping (Journal of the Pakistan Medical Association, 2020)
This clinical analysis of 125I seed implantation combined with Apatinib in the treatment of locally advanced lung cancer with negative driving genes was retrospectively performed on 19 patients in the Department of Thoracic Surgery, Tianjin First Central Hospital, from January 2018 to May 2019. Twelve cases were treated with Apatinib after 125I implantation, while the other seven were treated with 125I implantation only. IL-2R, IL-6 and TNF-? before and after the treatment, imaging changes every two months and related side effects were recorded. After the treatment, IL-2R, IL-6 and TNF-? of all the patients decreased in the first month, which was more obvious in combined therapy patients; the total effective rate in combined therapy patients was significantly higher than the others. There were no fatal complications, and all the side-effects were well tolerated by medical treatment. Continuous....